Cellulose and Its Derivatives: Applications, and Future Perspectives - Yao, Shuangquan (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Efficient separation of cellulose from lignocellulosic biomass is the premise of the high-value utilization of cellulose. The separated cellulose is mainly used in chemical, energy, and materials applications. The chemical applications of cellulose mainly consist of hydrolysis and fermentation. Polysaccharides are prepared from the hydrolysis of cellulose. Bioethanol is obtained from the fermentation of cellulose. The preparation of bio-oil is the main research direction of cellulose in the field of energy. In recent years, the excellent application value of cellulose has attracted attention. The preparation, modification, and application of nanocellulose and microcrystalline cellulose in polymer composites will be the main research trend in the future. This reprint helps readers understand and build on an overview of cellulose-based lignocellulose refining, especially in terms of efficient separation, functional modification, and promising applications. Thus, research including the current developments of the production methods, properties, and applications of cellulose and its derivatives are presented in this reprint.